Learning analysis of K-12 students' online problem solving: a three-stage assessment approach. Issue 2 (17th February 2017) - Hu, Yiling; Wu, Bian; Gu, Xiaoqing
ABSTRACT: Problem solving is considered a fundamental human skill. However, large-scale assessment of problem solving in K-12 education remains a challenging task. Researchers have argued for the development of an enhanced assessment approach through joint effort from multiple disciplines. In this study, a three-stage approach based on an evidence-centered design framework is proposed to analyze problem-solving behavior, abilities, and performance. The approach is applied to assess the online problem solving of 554 students in a Shanghai primary school. The study reveals four clusters with distinctive problem-solving behavior, abilities, and performance. The findings of this approach also corroborate the results of the Programme for International Student Assessment of Shanghai students' problem-solving performance. The implications and limitations of this study are also discussed.